Mercury in the atmosphere and in rainwater at Cape Point, South Africa. (January 2016) - Brunke, Ernst-Günther; Walters, Chavon; Mkololo, Thumeka; Martin, Lynwill; Labuschagne, Casper; Silwana, Bongiwe; Slemr, Franz; Weigelt, Andreas; Ebinghaus, Ralf; Somerset, Vernon
Abstract: Mercury measurements were concurrently made in air (Gaseous Elemental Mercury, i.e. GEM) as well as in precipitation samples (Total mercury, i.e. TotHg) over a seven year period (2007–2013) at Cape Point, South Africa, during the rainy seasons (May–October). Eighty-five rain events, almost exclusively associated with cold fronts, have been identified of which 75% reached the Cape Point observatory directly across the Atlantic Ocean from the south, while 19% moved in to the measuring site via the Cape Town metropolitan region. In statistic terms the GEM, TotHg, CO and 222 Rn levels within the urban-marine events do not differ from those seen in the marine rain episodes. Over the 2007–2013 period, the May till Oct averages for GEM ranged from 0.913 ng m −3 to 1.108 ng m −3, while TotHg concentrations ranged from 0.03 to 52.5 ng L −1 (overall average: 9.91 ng L −1 ). A positive correlation (R 2  = 0.49, n = 7) has been found between the average annual (May till October) GEM concentrations in air and TotHg concentration in rainwater suggesting a close relationship between the two species. The wetter years are normally associated with higher GEM and TotHg levels. Both GEM and TotHg annual means correlate positively with total annual (May till October) rain depths. If one or two outlier years are removed from the data set, the R 2 values increase from 0.23 to 0.10 for GEM and TotHg to 0.97 (n = 5) and 0.89 (n = 5), respectively. The relationship between annual mean GEM and annual precipitation depth also holds for the period 1996–2004 (R 2  = 0.6, n = 8) when GEM was measured manually (low resolution data). A positive correlation was also seen between annual average GEM concentrations and the El Niño Southern Oscillation (ENSO) Index (SOI), for the 1996–2004 period (R 2  = 0.7, n = 8). For the 2007–2013 periods this relationship was also positive but less pronounced. The relationship between annual precipitation depth and annual SOI suggests that the inter-annual variations of GEM (Hg0) concentration might be caused by large-scale meteorological processes. Graphical abstract: Highlights: Extended summary provided of GEM and THg measured at Cape Point, South Africa. Positive correlation observed bet-ween GEM and TotHg concentrations. Meteorological factors such as the El Niño Southern Oscillation (ENSO) contributed. Mercury emissions are influenced by increased biomass burning in drier seasons. Data presented provides novel information on atmospheric behaviour of mercury.